Addition of chayote pell flour in cookie: physico-chemical characterization and sensory analysis among children (Research, Society and Development, 2020)
The aim of the study was to evaluate the sensorial acceptability of cookie added from different levels of chayote pell flour (CPF). Also, determine the physico-chemical composition of the standard formulation and the one containing the highest CPF content with acceptance similar to the standard. Five cookie formulations were prepared: F1 (0% CPF) and the others added 6% (F2), 12% (F3), 18% (F4) and 24% (F5) of CPF. Participated in the sensory evaluation 61 untrained judges from 7 to 10 years old. Higher scores for appearance (p0.05) for the other samples. Formulation F4 was one with sensory acceptance similar to standard in sensory evaluation. Higher moisture, ash, protein and dietary fiber contents were observed in F4 and higher lipid, carbohydrate and calorie contents were observed in F1. It is concluded that a level of addition of up to 18% of CPF in cookie improves the nutritional profile of the product. In addition, it has acceptability similar to the standard product, with good commercialization expectations.